Layer‐by‐Layer Assembly of Cross‐Functional Semi‐transparent MXene‐Carbon Nanotubes Composite Films for Next‐Generation Electromagnetic Interference Shielding. (18th September 2018) - Weng, Guo‐Ming; Li, Jinyang; Alhabeb, Mohamed; Karpovich, Christopher; Wang, Hang; Lipton, Jason; Maleski, Kathleen; Kong, Jaemin; Shaulsky, Evyatar; Elimelech, Menachem; Gogotsi, Yury; Taylor, André D.
Abstract: Lightweight, flexible, and electrically conductive thin films with high electromagnetic interference (EMI) shielding effectiveness are highly desirable for next‐generation portable and wearable electronic devices. Here, spin spray layer‐by‐layer (SSLbL) to rapidly assemble Ti3 C2 T x MXene‐carbon nanotube (CNT) composite films is shown and their potential for EMI shielding is demonstrated. The SSLbL technique allows strategic combinations of nanostructured materials and polymers providing a rich platform for developing hierarchical architectures with desirable cross‐functionalities including controllable transparency, thickness, and conductivity, as well as high stability and flexibility. These semi‐transparent LbL MXene‐CNT composite films show high conductivities up to 130 S cm −1 and high specific shielding effectiveness up to 58 187 dB cm 2 g −1, which is attributed to both the excellent electrical conductivity of the conductive fillers (i.e., MXene and CNT) and the enhanced absorption with the LbL architecture of the films. Remarkably, these values are among the highest reported values for flexible and semi‐transparent composite thin films. This work could offer new solutions for next‐generation EMI shielding challenges. Abstract : Lightweight, flexible, and electrically conductive thin films with high electromagnetic interference shielding effectiveness are highly desirable for next‐generation portable and wearable electronic devices. Here, spin spray layer‐by‐layer is demonstrated to rapidly assemble Ti3 C2 T x MXene‐carbon nanotube composite films with desirable cross‐functionalities including controllable transparency, thickness, and conductivity, as well as high stability and flexibility.